Larangan Menikah Akibat Sumpah Akken Waghei Bedamei Adat Lampung Saibatin Perspektif Filosofi dan Sosiologi - Putri, Dian Eka; Jaelani, Abdul Qadir; Maharani, Cahya Kamila (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
The prohibition on marriage resulting from the Akken Waghei Bedamei oath in the Lampung Sai Batin tradition. This tradition gives rise to social and customary legal prohibitions, namely the prohibition on marriage between descendants of those who have taken the customary oath. Using a philosophical and sociological perspective, the values of the prohibition on marriage resulting from the Akken Waghei Bedamei oath can be examined. The purpose of this study is to analyze the philosophical and sociological perspectives on the prohibition on marriage resulting from the Akken Waghei Bedamei oath. This research is qualitative, using empirical juridical methods with a philosophical and sociological legal approach. From a philosophical perspective, noble values such as family honor, long-term peace, and the prevention of recurrent conflict are emphasized, but their implementation conflicts with the values of justice and the freedom of individual rights to choose a partner as long as they do not violate norms.